(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Injuries are, regrettably, an unavoidable hazard of sports participation. Although volleyball and beach volleyball are by most estimates relatively safe sports – particularly in comparison to other sports such as football (soccer) – epidemiologic research has revealed that volleyball athletes are at risk for certain types of injuries. Serious injuries which interfere with the athlete’s ability to participate have obvious immediate consequences (time lost from training and competition) and may have long term implications as well (chronic disability and functional limitation). Coaches and trainers should therefore have an understanding of the most common volleyball-related injuries in order to appreciate the potential impact injuries may have on the both on the athlete and the team. One of the first considerations in discussing the injuries for which volleyball athletes are at risk is to define what constitutes an injury. One accepted definition used in research is that an injury is any condition for which an athlete seeks medical attention. Injuries so defined may in turn be further subdivided into conditions that result in “time lost” from either competition or training and those that do not limit playing time. The length of time loss (typically reported in days or weeks) therefore provides a measure of injury severity that can be used to compare different types of injury. For example, in their 2004 study chronicling the injuries that occurred during one volleyball season in the Dutch professional league, Verhagen et al determined that shoulder injuries resulted in an average time lost from training or competition of 6.5 weeks – by far the longest mean absence from participation compared to other injury sites documented in their study.